Therapeutic effects following extracorporeal shock wave therapy for insertional and non-insertional Achilles tendinopathy - Hong Li; Wei Yao; Xiao'ao Xue; Yunxia Li; Yinghui Hua (Elsevier, 2023)
Background: The treatment for Achilles tendinopathy varies widely, and there is no consensus regarding the optimal treatment for both non-insertional and insertional Achilles tendinopathy. The purpose of this study was to evaluate the clinical efficacy of extracorporeal shock wave therapy (ESWT) in the treatment of insertional and non-insertional Achilles tendinopathy (AT). Methods: Sixty patients with AT were invited to participate in this study. Patients were allocated to one of two groups according to the site of the AT, including an insertional AT (IAT) group and a non-insertional AT (NIAT) group. ESWT was performed once a week for five weeks for both groups. The Victorian Institute of Sport Assessment-Achilles questionnaire (VISA-A) score and the visual analog scale (VAS) were used five times to evaluate the clinical outcomes, including before treatment, immediately after treatment, as well as one month, three months, and five years after treatment. Results: At three months after treatment, the IAT group exhibited a significantly higher VISA-A score (82 ± 6 vs. 76 ± 11; p = 0.01) and a significantly lower VAS score (1 ± 1 vs. 2 ± 1; p < 0.001) when compared with the NIAT group. At the five-year assessment, the IAT group (1 ± 1) had a significantly lower VAS score than the NIAT group (2 ± 1) (p = 0.02), while no significant difference for the VISA-A score was observed between the groups (84 ± 8 vs. 84 ± 10; p = 0.98). Conclusions: Extracorporeal shock wave treatment can improve the symptoms of both insertional and non-insertional AT. The IAT patients experienced better clinical outcomes compared with the NIAT patients.